2018
DOI: 10.1111/ecc.12867
|View full text |Cite
|
Sign up to set email alerts
|

Private health insurance and catastrophic health expenditures of households with cancer patients in South Korea

Abstract: This study examines the effects of private health insurance (PHI) on the incidence of catastrophic health expenditures (CHE) for households with a patient with cancer. This study uses 1-year data from 2013 and households with cancer patients as the unit of research rather than individual household members. The sample thus includes 468 households with members with cancer who also used emergency, outpatient and hospitalisation services. Households with PHI had a lower incidence of CHE for all thresholds than tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
5
8
1
Order By: Relevance
“…This is consistent with research findings that older patients who experienced unmet health care saw reduced HRQOL, and the more the patient shares his medical costs, the lower his HRQOL becomes. Furthermore, consistent with research findings, patients with BPH who have been continuously treated have a better HRQOL than those who have not regularly used health care [ 13 , 27 , 34 , 35 , 36 , 37 ]. Considering these findings, it is necessary to reduce the burden on the use of medical services by improving accessibility to health services for older patients with BPH.…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with research findings that older patients who experienced unmet health care saw reduced HRQOL, and the more the patient shares his medical costs, the lower his HRQOL becomes. Furthermore, consistent with research findings, patients with BPH who have been continuously treated have a better HRQOL than those who have not regularly used health care [ 13 , 27 , 34 , 35 , 36 , 37 ]. Considering these findings, it is necessary to reduce the burden on the use of medical services by improving accessibility to health services for older patients with BPH.…”
Section: Discussionsupporting
confidence: 82%
“…These findings are similar to those of a previous study, which indicated that those who have private medical insurance policies tend to receive outpatient and inpatient treatments. In line with these findings, among patients with chronic diseases who require continuous health care, those with private medical insurance have a reduced burden in terms of medical expenses, leading to better health-care outcomes [44][45][46]. Considering these results, there are limitations in managing chronic diseases with national health insurance only.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, there is a need to expand the scope of special cases in health insurance so that they are exempted from out-of-pocket payments for medical services and improve medical security for low-income groups. It is noteworthy that the incidence of catastrophic health expenditures is low among households with private health insurance [33]. In other words, private health insurance seems to be achieving its original goal of protecting households from excessive health expenditures.…”
Section: Discussionmentioning
confidence: 99%